All's well that ends well - "Shakespeare, William" (Sweet cherry publishing: China, 2013)
Another one of Shakespeare's witty comedies, this play is woven around Helena, the orphaned daughter of a famous physician, and Bertram, the son of her guardian. Helena is in love with Bertram, but he does not return her feelings. Nevertheless, Helena uses her intelligence to win Bertram as her husband
Keywords: Adaptations Juvenile literature